A Systematic Review of Pediatric and Adult In-Flight Medical Emergencies - Christina Sul; Sherif M. Badawy (International Journal of Pediatrics)
In-flight medical emergencies (IMEs) are acute onboard events of illnesses or injuries with potential immediate risk to a passenger’s short- or long-term health, or life. IMEs are significant events that are related to public safety concerns. With the increasing amount of annual air travel every year, it is expected that the number of encountered IMEs will continue to grow. Thus, it will be critical to develop and implement appropriate measures to manage IMEs with the best possible outcome. Despite the fact that most IMEs are self-limited with no serious adverse events, serious IME can lead to death, disability, or other unfavorable health outcomes, particularly as a result of suboptimal medical care. In this article, we systematically reviewed the published up-to-date evidence on the subject of in-flight emergencies with a specific focus on pediatric population.